A review of a diazepam nasal spray for the treatment of acute seizure clusters and prolonged seizures. (2nd November 2021) - Higdon, Lindsay M.; Sperling, Michael R.
ABSTRACT: Introduction: Some people with epilepsy experience acute repetitive seizures (ARS), also termed seizure clusters, which have a negative impact on patient and caregiver quality of life, emotional wellbeing, daily function, and may pose risk of injury or death. In addition, these events increase healthcare utilization in emergency departments and hospitals, which might be avoided with use of an at-home rescue medication. Intranasal formulations of benzodiazepines used as rescue medications provide a means of delivering rescue medication that is socially acceptable and more easily administered than rectal drug. Areas covered: This article provides a review of intranasal diazepam covering development, pharmacokinetics, dosing, safety, adverse effects, and efficacy. The authors compare it with rectal diazepam and intranasal midazolam. Expert opinion: Intranasal rescue drugs are a valuable treatment modality for seizure clusters and prolonged seizures that are effective and well tolerated with the potential to enhance patient quality of life, reduce the incidence of seizure-related injury, and lessen the need for hospital visits. The literature does not provide evidence comparing the various rescue agents, and head-to-head comparison studies are needed. An inhaled benzodiazepine as a seizure rescue drug is currently undergoing clinical trials.